SmartEN - Smart management for sustainable built environment including bridges, structures and infrastructure systems - Onoufriou, Toula; Berberidis, Kostas; Chryssanthopoulos, Marios K.; Kalis, Antonis; Kyriakides, Marios (My University, 2012)
This paper presents the research and training focus of major European Marie Curie Initial Training Network research programme, SmartEN, which focuses on the development of effective smart proactive management methods for sustainable built and natural environment. The SmartEN research focuses on multi-disciplinary developments combining mainly the areas of proactive management, non-destructive evaluation methods from the civil engineering discipline, with wireless sensor networks, signal processing and communication technologies from the electrical engineering. Recent emerging technologies in miniature wireless sensor platforms which utilize novel digital signal processing offer new opportunities for continuous monitoring of complex systems. These developments open up a completely novel area for multi-disciplinary research towards the 'smart' management of sustainable environment. The SmartEN ITN Marie Curie Programme aims to push innovation through effective development and integration of emerging technologies targeting key application areas of current interest to Europe and worldwide. These include smart proactive management of structural systems such as tall buildings, bridges including long span modern bridges and heritage bridges, transportation infrastructure networks and urban micro-climate as this affects urban structures and infrastructure networks.
Keywords: Built environment series; Civil engineering; Structural Systems Research Project